Seasonal Variations in Ostracod Community Structure and Physicochemical Parameters in Khanki Headworks, Pakistan: Seasonal Variations in Ostracod Community - Raza, Muhammad Ahsan; Roohi , Nabila; Ahmad, Husna (Pakistan BioMedical Journal, 2023)
Protozoans, rotifers, ostracods and copepods are principal groups of zooplanktons. These organisms are crucial biotic elements, and impact all functional features of aquatic ecosystems. Objective: To assess the impacts of environmental variables on the abundance, biodiversity and seasonal distribution of ostracods in Khanki Headworks, Pakistan. To evaluate the contribution of ostracods as bio-monitors of contamination in freshwater ecosystems. Methods: Month wise separate water samples were taken for different environmental variables from four sampling sites (each with 3 sub-sites), for study period of one year (February 2021 to January 2022), whereas, samples of microcrustaceans (ostracods) were collected with planktonic net (mesh size: 37µm). Results: In total, 5 species of ostracods, associated to 4 genera and 2 families were identified from February 2021 to January 2022. Heterocypris incongruence was the most abundant species, whereas, Dolerocypris sinensis was noted as least abundant species. Ostracods abundance and biodiversity were monitored highest in June and minimum in the month of January. Results of Pearson correlation showed that physicochemical parameters, electrical conductivity (EC), temperature, turbidity, total dissolved solids (TDS) and pH have positive effects on the density and diversity of ostracods. In contrast, dissolved oxygen (DO) showed negative relationship with the abundance and diversity of planktonic ostracods. These findings were further validated by Canonical correspondence analysis (CCA). Conclusions: This investigation revealed that physicochemical parameters generally govern the population dynamics of ostracods.